COMPACT CPW FED ANTENNA HAVING DUAL AND INVERTED BEAKER SHAPED FOR WLAN/WIMAX OPERATIONS (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In recent years, great interest is focused on microstrip antennas for their small volumes, low profiles, good integration, low costs and good performance. With the continuous growth of wireless and mobile communication service and the constant miniaturization of communication equipment, there are higher demands for the volume of antennas, integration and working band. This paper presents a basic rectangular shaped microstrip patch antenna for wireless communications system which is suitable for 4.54 GHz to 5.632 GHz band operations. These systems may include upper higher bands of WiMAX (Worldwide Interoperability for Microwave Access) and wireless local-area network (WLAN). A rectangular ring slot is cut and double T shape along with one inverted beaker slot is embedded into it. Besides that, in the inverted beaker shape, similar shape slot is cut. This design has several advantages such as compact size, omnidirectional radiation pattern etc. which all are studied. The results confirm good performance of the single and multiband antenna design.